The implications of Singapore's regionalization program on Singapore banks - Chong, Juliana Kim Kian (2015)
The high growth prospects of neighbouring countries have been repeatedly emphasized through the media over the last three years and as the drive to go regional becomes evident, it is imperative that the changing role of banks, both in the domestic economy as well as in the region, be explored. Singapore's Regionalization Program is expected to significantly change the structure, operational demands, and potential profitability of the banks in Singapore. The aim of this project is to examine the reasons why Singapore banks need to go regional and the implications for this expansion abroad. The widening contrast between the limited potential in the local market and the bountiful opportunities existing in the region will induce Singapore banks to expand abroad aggressively over the next few years. With regionalization, the related growth, profitability, and risk management issues come to the forefront of the agenda for top level bank managers. A survey was therefore conducted among top level bank managers to gather consensus opinions about the key issues in the regionalization process. The project also highlights the more recent potential areas of growth and profitability like venture capital, project financing and loan syndication, and private banking as well as the problems and risks faced by Singapore banks in their regional expansion. The survey results indicated that the recruitment of qualified personnel in the regional market, difficulties in assessing credit quality of bank instruments, and regulatory restrictions continue to be main areas for bankers as they regionalize. Singapore banks, in seeking to regionalize should identify the niche areas where they have strengths and establish the optimal level of risk they are willing to take in each new market. The ability to redress their deficiencies as compared to foreign banks will have a vital impact on the future success as regional banking players.